2008
DOI: 10.1038/pcan.2008.34
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen gauge needles improve specimen quality but not cancer detection rate in transrectal ultrasound-guided 10-core prostate biopsies

Abstract: Performance of 16 (16 g) (n ¼ 103) and 18 gauge (18 g) (n ¼ 101) biopsy needles in transrectal ultrasound (TRUS)-guided 10-core prostate biopsies were compared in terms of cancer detection and pre-defined specimen quality criteria in this prospective randomized study. Cancer detection rates of the two groups were similar, although the mean core volume of 16 g needles was almost twice that of 18 g needles. On the other hand, using 16 g needles significantly improved specimen quality by acquiring less empty core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…These findings are not in line with a similar experience reported by Inal et al [5] who observed that the quality of samples was better using a 16-gauge needle. In both studies, fragmentation was one of the quality outcomes because it impedes to assess correctly the cancer quantity in sampling and to determine clearly the GS [13].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…These findings are not in line with a similar experience reported by Inal et al [5] who observed that the quality of samples was better using a 16-gauge needle. In both studies, fragmentation was one of the quality outcomes because it impedes to assess correctly the cancer quantity in sampling and to determine clearly the GS [13].…”
Section: Discussioncontrasting
confidence: 88%
“…On the other hand, it can potentially carry a higher risk of procedure-related complications. Few studies to date have addressed this specific issue [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…The fragmentation of needle‐core biopsies complicates the interpretation of prostate biopsy cores. One contributing factor to fragmentation of needle cores during biopsy is the needle core length [1,2]. Little is known as to whether there are other controllable factors that contribute to fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Fink et al (28) reported that 16-gauge needles increased the cancer detection rate ex vivo. However, Inal et al (29) concluded that despite the fact that the mean core volume of the 16-gauge needle was almost twice that of the 18-gauge needle, cancer detection rates for the two groups were similar regarding the 10-core prostate biopsy procedures. The advantage of the 16-gauge needle was considered to be improved specimen quality as a result of acquiring less empty cores, small cores and fragmented cores.…”
Section: Discussionmentioning
confidence: 99%